Clinical study of Tinea capitis in Northern Karnataka: A three-year experience at a single institute - Pai, Varadraj V. (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Tinea capitis is a superficial fungal infection of the hair follicle of scalp. Most of the dermatophytosis do not have such age propensity as tinea capitis which almost invariably involves the paediatric age group. The exact incidence of tinea capitis is not known. This study is done in order to isolate the species variation in an area, to know the changing patterns of occurrence of different species and their association with clinical pattern MATERIALS AND METHODS: All clinically diagnosed cases of tinea capitis which presented to our out patient department over a period of one year were included in the study. RESULTS: 70 cases of Tinea capitis were studied. DISCUSSION: Tinea capitis is a disease of prepubertal children with common in age group of 5- 15 years. The incidence varies from 0.5% to 10%. Most common presenting feature was alopecia.